Analisis Ayat Riba dalam Tafsir Al-Azhar Karya Buya Hamka - A. Syafi' AS. (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2018)
This study aims to examine the verses of Riba in Tafsir al-Azhar by Buya Hamka. To capture the contextual meaning that is formed in the Interpretation, the author considers it important to discuss it in this study. This type of research is qualitative descriptive. Considering that this study is about understanding the verses of the Qur'an by analyzing the interpretation of the commentaries, then methodologically this research is categorized as explorative research, meaning understanding the verses of al-Qu'an related to the problem of Riba. The technique of collecting data is documentary study. While the data analysis technique uses critical analytical techniques, with deductive and inductive thinking techniques. The results of the study can be summarized as follows: First; in Surat al-Baqarah: 278, in the word